Principles for Soft-Hardware Complex Development to Increase Efficiency of Power Transformers - A. L. Trushnikov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper reveals principles for development and operation of soft-hardware complex which is designed to control transformer substations of industrial enterprisers. Purpose of soft-hardware components of the complex is considered in the paper.Development and application of such complex allow to increase an efficiency of power transformer resource and decrease electric power losses in the elements of power-supply system at industrial enterprisers.